2021
DOI: 10.1111/ijcp.14253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of medication adherence among patients with chronic diseases in Saudi Arabia

Abstract: Poor medication adherence is a global problem that compromises the benefit of a given treatment. 1 It also increases the rate of mortality, morbidity and healthcare costs. 2 In the United States, direct medical cost of chronic diseases reached a trillion dollar, while nonadherence costs over $170 billion annually. 2,3 Furthermore, in transplant recipients, the non-adherence to immunosuppressants results in 1319 cases of renal transplant failure annually. 4 The achievement of the total benefit from medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…The questionnaire was adapted from a previous study by Prabahar K et al [ 14 ]. Experts provided their feedback and opinions for improving the questionnaire, and their suggestions were incorporated into the final questionnaire, which contained 15 questions and was designed using online cloud-based questionnaire development software (Google Forms).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire was adapted from a previous study by Prabahar K et al [ 14 ]. Experts provided their feedback and opinions for improving the questionnaire, and their suggestions were incorporated into the final questionnaire, which contained 15 questions and was designed using online cloud-based questionnaire development software (Google Forms).…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was calculated using Slovin’s formula, with a population size of 385 patients with chronic diseases in Saudi Arabia from a recently published study by Kurdi S et al 2021, with a confidence interval (CI) of 95% and a margin of error of 5% [ 14 ]. Social media channels were used to distribute the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elderly patients are more prone to have chronic conditions and use many medications, increasing medication complications. The majority of patients had more than one chronic disease, according to a recent cross-sectional study conducted in Saudi Arabia, and the pharmaceutical dose type and dosing schedule were independent predictors of medical adherence [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prescription of complex medication regimens is widespread in healthcare centers [16][17][18]. Thus, simplifying medication regimens and educating them in sufficient time and efficient communication help in increasing the satisfaction, perception, and continuity of medication and adherence [19][20][21][22]. A study conducted in Riyadh interviewed 511 adult participants and aimed to assess the understanding of prescription label instructions for five commonly prescribed medications and concluded that misunderstanding was common among these participants [11].…”
Section: Introductionmentioning
confidence: 99%